2014
DOI: 10.1111/hcre.12050
|View full text |Cite
|
Sign up to set email alerts
|

The Dual Role of Morally Ambiguous Characters: Examining the Effect of Morality Salience on Narrative Responses

Abstract: Using social comparison theory as a framework, 2 experiments examined the effects of a person's self-perception on responses to characters who display varying levels of morality. Study 1 found that individuals whose vices were made salient felt more positive affect and enjoyment after reading a narrative featuring a morally ambiguous character (MAC) than one featuring a bad character. Study 2 found that individuals whose virtues were made salient felt more positive affect and enjoyment after reading a narrativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 39 publications
0
22
1
Order By: Relevance
“…For example, Superman—a quintessential superhero—should be more quickly categorized as “hero” than Deadpool—an antihero. Various permutations of this procedure could help determine whether antihero characters (and other morally ambiguous characters [MACs]) are a subordinate category of the basic category “hero” or whether these characters fit into their own basic category distinct from both heroes and villains (see Krakowiak & Oliver, 2012; see also Krakowiak & Tsay-Vogel, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Superman—a quintessential superhero—should be more quickly categorized as “hero” than Deadpool—an antihero. Various permutations of this procedure could help determine whether antihero characters (and other morally ambiguous characters [MACs]) are a subordinate category of the basic category “hero” or whether these characters fit into their own basic category distinct from both heroes and villains (see Krakowiak & Oliver, 2012; see also Krakowiak & Tsay-Vogel, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…There is a growing focus within narrative research on MACs, such as antiheroes (see Eden, Daalmans, & Johnson, 2016; Eden, Grizzard, & Lewis, 2011; Janicke & Raney, 2015; Krakowiak & Oliver, 2012; Krakowiak & Tsay-Vogel, 2013, 2015; Raney & Janicke, 2013). A combination of our approach with this past work might yield novel predictions.…”
Section: Discussionmentioning
confidence: 99%
“…Justification of violence. The growing prevalence of morally ambiguous protagonists in entertainment narratives suggests the importance of examining violence from a moral perspective (Krakowiak & Tsay-Vogel, 2015). According to Bandura, Barbaranelli, Caprara, and Pastorelli (1996), individuals engage in moral disengagement to exert control over their moral self-regulation process.…”
Section: Violence On Tvmentioning
confidence: 99%
“…MACs are often described by what they are not: purely good or bad (e.g., Krakowiak & Tsay-Vogel, 2015). It is usually suggested that MACs are those characters who engage in both good and bad moral actions (Krakowiak & Oliver, 2012;Krakowiak & Tsay, 2011;Krakowiak & Tsay-Vogel, 2013, 2015Tsay & Krakowiak, 2011;Tsay-Vogel & Krakowiak, 2016), or those who enact both prosocial and antisocial behaviors (Krakowiak & Oliver, 2012;Tsay-Vogel & Krakowiak, 2016).…”
Section: Morally Ambiguous Characters (Macs)mentioning
confidence: 99%